In vivo analysis of ankle joint kinematics and ligament deformation of chronic ankle instability patients during level walking - Ruan, Yaokuan; Wang, Shengli; Zhang, Nan; Jiang, Zhende; Mei, Nan; Li, Pu; Ren, Lei; Qian, Zhihui; Chang, Fei (Frontiers in Bioengineering and Biotechnology, 2024)
Chronic ankle instability (CAI) carries a high risk of progression to talar osteochondral lesions and post-traumatic osteoarthritis. It has been clinically hypothesized the progression is associated with abnormal joint motion and ligament elongation, but there is a lack of scientific evidence. A total of 12 patients with CAI were assessed during level walking with the use of dynamic biplane radiography (DBR) which can reproduce the in vivo positions of each bone. We evaluated the uninjured and CAI side of the tibiotalar and subtalar joint for three-dimensional kinematics differences. Elongation of the anterior talofibular ligament (ATFL), calcaneofibular ligament (CFL), and posterior talofibular ligament (PTFL) were also calculated bilaterally. For patients with CAI, the dorsiflexion of the tibiotalar joint had reduced (21.73±3.90° to 17.21±4.35°), displacement of the talus increased (2.54±0.64mm to 3.12±0.55mm), and the inversion of subtalar joint increased (8.09±2.21° to 11.80±3.41°). Mean ATFL elongation was inversely related to mean dorsiflexion angle (CAI: rho=-0.82, P<0.001; Control: rho=−0.92, P<0.001), mean ATFL elongation was related to mean anterior translation (CAI: rho=0.82, P<0.001; Control: rho=0.92, P<0.001), mean CFL elongation was related to mean dorsiflexion angle (CAI: rho=0.84, P<0.001; Control: rho=0.70, P<0.001), and mean CFL elongation was inversely related to mean anterior translation (CAI: rho=-0.83, P<0.001; Control: rho=-0.71, P<0.001). Furthermore, ATFL elongation was significantly (CAI: rho=-0.82, P<0.001; Control: rho=-0.78, P<0.001) inversely correlated with CFL elongation. Patients with CAI have significant changes in joint kinematics relative to the contralateral side. Throughout the stance phase of walking, ATFL increases in length during plantarflexion and talar anterior translation whereas the elongation trend of CFL was the opposite. This understanding can inform the development of targeted therapeutic exercises aimed at balancing ligament tension during different phases of gait. The interrelationship between two ligaments is that when one ligament shortens, the other lengthens. Surgeons might consider positioning the ankle in a neutral sagittal plane to ensure optimal outcomes during ATFL and CFL repair. The occurrence of CAI didn’t change this trend.